Efficacy and safety of direct-acting antiviral agents when combined with secukinumab. Issue 1 (20th May 2017) - Martinez-Santana, Virginia; Rodriguez-Murphy, Esther; Smithson, Alex; Miserachs-Aranda, Nuria; del Río-Gil, Ruben; Torre-Lloverás, Inmaculada
Abstract : Background: The interference in the immune response induced by biological disease-modifying antirheumatic drugs (bDMARDs) increases the risk of reactivation of infections. Treatment of patients with chronic hepatitis C virus (HCV) infection and psoriasis is complex. The efficacy and safety of the new direct-acting antiviral agents (DAA) when combined with bDMARDs remain unknown. Case report: We present a case of a 44-year-old Caucasian man affected with psoriasis and HCV infection. Throughout the course of the psoriatic disease, this patient received several lines of treatment, including secukinumab, a new type of bDMARD. At the time of commencing secukinumab, new DAA agents (ledipasvir/sofosbuvir) were also initiated. At week 12 post-treatment, hepatitis C viral load was undetectable and the patient remained in remission of psoriasis. Conclusion: This case report suggests that secukinumab is a therapeutic option in patients with psoriasis, particularly in those cases with HCV infection where treatment with DAA agents is warranted.